Insuring against Health Shocks: Health Insurance and Household Choices - Kai Liu (Institute for the Study of Labor (IZA), 2015)
This paper provides empirical evidence on the role of public health insurance in mitigating adverse outcomes associated with health shocks. Exploiting the rollout of a universal health insurance program in rural China, I find that total household income and consumption are fully insured against health shocks even without access to health insurance. Household labor supply is an important insurance mechanism against health shocks. Access to health insurance helps households to maintain investment in children's human capital during negative health shocks, which suggests that one benefit of health insurance could arise from reducing the use of costly smoothing mechanisms.
Keywords: D1; O1; I1; 330; China; health insurance; health shock